Microsoft Visual C# 2008 step by step - Sharp, John. (Redmond, Wash. : Microsoft Press, 2008)
Covers the fundamentals of Visual C# and how to use it to build .NET-connected applications, covering topics including syntax, Web services, and operators.
Keywords: Microsoft Visual C# .NET (Computer software); C# (Computer program language); Visual programming (Computer science); C# (Computer language)